Podcast Sebagai Media Ajar Dalam Pembelajaran Pendidikan Agama Islam - Ahmad Husein; Eidel Putri Maharani; Muhammad Amril Saifuddin; Angga Bagas Satria; Unik Hanifah Salsabila (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
As time goes by, social media can also be used as a learning medium, there are lots of learning media that can be used by teachers, such as Podcast media on the Spotify application. In the Spotify application there is a feature that can be used to create learning media, namely Podcasts. Therefore, learning PAI using the Spotify Podcast will make students more interested and easier to understand the learning material by playing it many times in the application. This research uses a qualitative method with a literature study approach. Data collection techniques use library data by collecting research related to the topic. Implementing the Podcast feature on Spotify can be a new step for educators/teachers, and is easy to provide students with an understanding of PAI learning.